Receiver Design to Employ Simultaneous Wireless Information and Power Transmission with Joint CFO and Channel Estimation; IEEE Access; Vol. 7 - Razharam A. Akashkumar; Ruy D. Dinis; Dzhayakodi (Jayakody) Arachshiladzh D. N. K. Dushanta Nalin Kumara; Kumar N. Niradzh (2019, 2019)
Title screen